Plasma Steroid Dynamics in Late- and Near-term Naturally and Artificially Conceived Bovine Pregnancies as Elucidated by Multihormone High-resolution LC-MS/MS - Martins-Junior, Helio A.; Pinaffi, Fabio L. V.; Simas, Rosineide C. [UNESP]; Tarouco, Adriana K.; Ferreira, Christina R.; Silva, Luciano A.; Nogueira, Guilherme P. [UNESP]; Meirelles, Flavio V.; Eberlin, Marcos N.; Perecin, Felipe (Endocrine Soc, 2014)
The plasma levels of corticosteroids and sex steroids during pregnancy are key indicators of mammalian placental function and the onset of parturition. Steroid hormones are believed to be disturbed in pregnancies produced using assisted reproductive technologies (ARTs) due to placental dysfunction and the frequently observed lack of parturition signals. To elucidate the plasma steroid dynamics, a liquid chromatography-tandem mass spectrometry method was developed and used to determine the levels of corticosteroids (corticosterone, 11-deoxycortisol, and cortisol) and their direct precursors (progesterone and 17 alpha-OH-progesterone) as well as sex steroids (androstenedione, estrone, estrone sulfate, testosterone, and 17 beta-estradiol) in bovine plasma. The levels of these 10 steroids in recipient cows carrying naturally conceived (control), in vitro fertilized (IVF), or cloned (somatic cell nuclear transfer) conceptuses were compared during late-term pregnancy (30 days before parturition), during near-term pregnancy (1 day before parturition), and on the day of parturition (day 0). Significant differences were observed among the corticosteroid levels: higher levels of corticosterone, 11-deoxycortisol, and cortisol were detected in cloned pregnancies at day 30; lower levels of corticosterone were observed in ART-derived pregnancies at days 1 and 0; and estrone and estradiol levels were higher in IVF pregnancies through out the final development. These results suggested an upregulation of the P450(C11) and P450(C21) enzymes 30 days before parturition in somatic cell nuclear transfer pregnancies and an over-activation of the aromatase enzyme in IVF pregnancies. Taken together, the monitoring of multiple steroid hormones revealed that the pregnancies obtained using ART exhibited plasma steroid concentration dynamics compatible with the dysregulation of steroidogenic tissues.